2006
DOI: 10.1155/2006/368648
|View full text |Cite
|
Sign up to set email alerts
|

Non‐equivalent greedy and almost greedy bases in lp

Abstract: Abstract. For 1 < p < ∞ and p = 2 we construct a family of mutually non-equivalent greedy bases in p having the cardinality of the continuum. In fact, no basis from this family is equivalent to a rearranged subsequence of any other basis thereof. We are able to extend this statement to the spaces Lp and H1 . Moreover, the technique used in the proof adapts to the setting of almost greedy bases where similar results are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The novelty in our approach has to be seen also in that our techniques are valid for the limit case p = 1. This nicely complements the main result from [8], where Dilworth et al showed that if 1 ≤ p < ∞ then ℓ p has a continuum of permutatively non-equivalent almost greedy bases.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The novelty in our approach has to be seen also in that our techniques are valid for the limit case p = 1. This nicely complements the main result from [8], where Dilworth et al showed that if 1 ≤ p < ∞ then ℓ p has a continuum of permutatively non-equivalent almost greedy bases.…”
Section: Introductionsupporting
confidence: 80%
“…The following was result was proved for the case ℓ 1 in [8] using completly different techniques. Corollary 6.11.…”
Section: For Every Concave Increasing Functionmentioning
confidence: 91%
“…For instance, in light of [24,Theorem 2.1], this technique can be applied to the L p -normalized Haar system to obtain a bidemocratic conditional quasi-greedy basis of L p ([0, 1]), p ∈ (1, 2) ∪ (2, ∞). Also, since, for the same values of p, the space ℓ p has a greedy basis which is non-equivalent to the canonical basis (see [14,Theorem 2.1]), this technique yields a bidemocratic conditional basis of ℓ p .…”
Section: Building Bidemocratic Conditional Quasi-greedy Basesmentioning
confidence: 99%
“…In between these two extremes we come across spaces like ℓ p for 1 < p < ∞, p = 2, with a unique symmetric basis and a wealth of permutatively non-equivalent greedy bases (cf. [10]). The following question naturally arises: Problem 1.2.…”
Section: N=1mentioning
confidence: 99%
“…For instance, Smela proved that the L p -spaces for 1 < p < ∞, p = 2, and H 1 have infinitely many permutatively non-equivalent greedy bases [33] (cf. [10]).…”
Section: N=1mentioning
confidence: 99%